The take-up of means-tested benefits, 1984 - 90 - Vanessa Fry; Graham Stark (Institute for Fiscal Studies (IFS), 1993)
A report considering how effective means-tested benefits are at reaching the right people. The most comprehensive study of take-up ever undertaken, it gives a detailed breakdown of the results.
Keywords: 330